A comparative study of robotics and laparoscopic in minimally invasive pancreatoduodenectomy: A single-center experience - Zong, Ke; Luo, Kai; Chen, Kunlun; Ye, Jianwen; Liu, Wentao; Zhai, Wenlong (Frontiers in Oncology, 2022)
Objective: To retrospectively compare the short-term benefits of robotic surgery and laparoscopy in the perioperative period of minimally invasive pancreatoduodenectomy (MIPD). Methods: This retrospective analysis evaluated patients who underwent laparoscopic pancreaticoduodenectomy (LPD) or robotic pancreaticoduodenectomy (RPD) from March 2018 to January 2022 in the First Affiliated Hospital of Zhengzhou University (Zhengzhou, China). Perioperative data, including operating time, complications, morbidity and mortality, estimated blood loss (EBL), and postoperative length of stay, were analysed. Result: A total of 190 cases of MIPD were included, of which 114 were LPD and 76 were RPD. There was no significant difference between the two groups in gender, age, previous history of upper abdominal operation, jaundice (>150 µmol/L) or diabetes (P > 0.05). The conversion rate to laparotomy was similar in the LPD and RPD groups (5.3% vs. 6.6%, P=0.969). A total of 179 cases of minimally invasive pancreatoduodenectomy were successfully performed, including 108 cases of LPD and 71 cases of RPD. There were significant differences between the laparoscopic and robotic groups in operation time [mean, 5.97 h vs. 5.42 h, P < 0.05] and postoperative length of stay [mean, 15.3 d vs. 14.6 d, P < 0.05]. No significant difference was observed between the two groups in terms of EBL, intraoperative transfusion, complication rate, mortality rate, or reoperation rate (P > 0.05). There were no significant differences in pathological type, number of lymph nodes harvested or positive lymph node rate (P > 0.05). Conclusion: RPD had an advantage compared to LPD in reduced operation time and postoperative length of stay, technical feasibility and safety.